Theoretical study on wire-electro discharge machining process for nickel-base alloys - Tay Phaik Kean (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
The objective of this study was machining the advance material, Nickel-base Alloy by using the Wire-cut EDM. The Taguchi method (Design of Experiments) have been use to design the experiment.